Effects of Exercise Training on the Paracrine Function of Circulating Angiogenic Cells - Evans, William S.; Sapp, Ryan M.; Kim, Katherine I.; Heilman, James M.; Hagberg, James; Prior, Steven J. (International Journal of Sports Medicine, 2020)
Exercise training has various benefits on cardiovascular health, and circulating angiogenic cells have been proposed as executing these changes. Work from the late 1990s supported an important role of these circulating post-natal cells in contributing to the maintenance and repair of the endothelium and vasculature. It was later found that circulating angiogenic cells were a heterogenous population of cells and primarily functioned in a paracrine manner by adhering to damaged endothelium and releasing growth factors. Many studies have discovered novel circulating angiogenic cell secreted proteins, microRNA and extracellular vesicles that mediate their angiogenic potential, and some studies have shown that both acute and chronic aerobic exercise training have distinct benefits. This review highlights work establishing an essential role of secreted factors from circulating angiogenic cells and summarizes studies regarding the effects of exercise training on these factors. Finally, we highlight the various gaps in the literature in hopes of guiding future work.
Keywords: microRNA; angiogenesis; extracellular vesicle; cytokine